Managing Multicultural Society in Indonesia - Riwanto Tirtosudarmo (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2022)
This paper attempts to employ several concepts develop in the west to resolve social and political conflict in a multicultural society. The concept of interculturalism recently proposed as an alternative to the concept of multiculturalism and its related policy considered as a failure will be reviewed to get the perspective to view multicultural problems in Jakarta. In the wake of a recent local election, Jakarta has been rocked by a series of demonstration by Islamic groups against Basuki Tjahaja Purnama (Ahok) the Jakarta’s mayor, a Chinese-Christian that accused to denigrate Islam in one of his speech. After a heated campaign from both sides, Basuki who run for the second term controversially lost in a small margin to Anis Baswedan, his rival, an Arabic descent and a Muslim. The election was highly contentious as the supporter of Anies aggressively using Islam as the rallying cry to defeat Ahok. The political development that shows the increasing political pressures from the Islamic groups alarmingly polarized the population into sectarian politics and breaking up the previously multi-cultural coexistence. The multi-cultural issues in Jakarta, the capital city of Indonesia, a Muslim majority country, could provide a good case of problem in governing a culturally diverse country, in the non-Western society. What is the hindrance in employing the Western concept, particularly citizenship, given the different historical trajectory for such an urban multicultural society like Jakarta? The paper would like to contribute into the debate on the problem of multicultural society from the experience of a non-Western country.